2021
DOI: 10.1186/s40001-021-00618-3
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation support for SARS-CoV-2: a multi-centered, prospective, observational study in critically ill 92 patients in Saudi Arabia

Abstract: Background Extracorporeal membrane oxygenation (ECMO) has been used as a rescue strategy in patients with severe with acute respiratory distress syndrome (ARDS) due to SARS-CoV-2 infection, but there has been little evidence of its efficacy. Objectives To describe the effect of ECMO rescue therapy on patient-important outcomes in patients with severe SARS-CoV-2. Methods A case series study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Two congenital diaphragmatic studies found contrasting results (153, 154) and two obstetric studies showed higher ECMO use in patients from diverse backgrounds (155, 156). None examined language and only one Saudi Arabian study examined immigration status with greater ECMO utilization with legal (vs illegal) entry but higher use in non-nationals (vs Saudi Arabians) (157).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two congenital diaphragmatic studies found contrasting results (153, 154) and two obstetric studies showed higher ECMO use in patients from diverse backgrounds (155, 156). None examined language and only one Saudi Arabian study examined immigration status with greater ECMO utilization with legal (vs illegal) entry but higher use in non-nationals (vs Saudi Arabians) (157).…”
Section: Resultsmentioning
confidence: 99%
“…Individual-level primary themes were: 1) differential access to care (28, 30, 33, 106, 114, 122, 168, 170), 2) varying clinical presentations (26, 27, 30, 31, 80, 92, 128, 161, 168), 3) different religious/cultural preferences (26, 27, 80, 89, 93, 168), or other unmeasured individual SDoH as confounders (30, 84, 96). Hospital-level mechanisms included: 1) provider-level treatment variation (26, 31, 80, 93, 167, 169) and 2) between-hospital variability in offering ECMO, timing of initiation, organizational structure, experience, and standardized care practices/processes (27, 30, 31, 80, 90, 106, 122, 123, 129–131, 154, 157, 161, 168–173). Specific systemic/structural factors such as legal frameworks, economic systems, and social policies included: 1) healthcare system adequacy (pay-for-performance measures [31, 122], disparate insurance access and quality [28, 32, 106, 128, 167] and, in countries with universal healthcare, need for enhanced systems to serve marginalized communities [30, 110, 114, 117]) and 2) geographic centralization, balancing consolidated expertise, and quality with accessibility of time-critical technology (106, 171–174).…”
Section: Resultsmentioning
confidence: 99%
“…Barotrauma has been shown to be quite prevalent in COVID-19 patients. Pneumothorax has been identified in up to 20% of mechanically ventilated patients and to almost 30% of patients on ECMO [ 30 , 31 , 32 ]. It is noteworthy that our patients with fungal infections more frequently had barotrauma (68.4% vs. 18.9%), which included pneumothorax, pneumomediastinum, and subcutaneous emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical characteristics of the groups with and without bleeding events are shown in Table 1. In this study, body mass index (BMI) of 30 kg/m 2 or greater was used as a cutoff value for high vs. normal weight because moderate or severe obesity (BMI greater than or equal to 30 kg/m 2 ) has been reported as a risk factor for severe COVID-19 infection [14,15]. Hypertension, diabetes mellitus, cardiovascular disease, chronic obstructive pulmonary disease, and chronic kidney disease were evaluated as comorbidities because they are also known as risk factors [14,16].…”
Section: Assessment Of Patient Characteristics Immediately Prior To Ecmomentioning
confidence: 99%
“…In this study, body mass index (BMI) of 30 kg/m 2 or greater was used as a cutoff value for high vs. normal weight because moderate or severe obesity (BMI greater than or equal to 30 kg/m 2 ) has been reported as a risk factor for severe COVID-19 infection [14,15]. Hypertension, diabetes mellitus, cardiovascular disease, chronic obstructive pulmonary disease, and chronic kidney disease were evaluated as comorbidities because they are also known as risk factors [14,16]. The hospitalization period was defined as the duration from the date of admission to that of discharge, but all enrolled patients were transferred to other hospitals to continue their treatment after completing ECMO therapy because our hospital is a tertiary referral center.…”
Section: Assessment Of Patient Characteristics Immediately Prior To Ecmomentioning
confidence: 99%